Frank, Joe & Co. - Bouchez, Hilde; Demeester, Ann; Gabriel, Thomas; Gehry, Frank O.; Hoet, Jan; Scanlan, Joe; Exhibition. Frank, Joe & Co.. Gebäude der Post Herford. MARTa Herford. 2001-05-05. 2001-07-08 (Herford : MKK gGmbH, 2001)
Scarpa, Tobia & Afra ; Hebbelinck, Pierre ; Kleihues, Josef Paul ; Gehry, Frank O. ; Peichl, Gustav ; Dauner, Peter-Michael ; Staab, Volker ; Architekten Schweger+Partner ; Beaudouin, Laurent ; Bayard, Yves ; Vidal, Henri ; Gamberini, Italo ; Bacchi, Alberto ; Sarteanesi, Tiziano ; Siza, Alvaro ; architectenbureau ir. A. Cahen bv ; Rossi, Aldo ; O.M.A. ; Beel, Stéphane ; Achtergael, Lieven ; Körmeling, John ; Tesar, Heinz ; Meier, Richard
publ. SMAK : zie kast leeszaal
Duits
Engels
boek